Adverse Drug Reaction: A Common Dermatological Emergency - Khondker, Lubna; Wahab, Md Abdul; Khan, Md Shirajul Islam (Bangladesh Journal of Medicine, 2013)
In the evaluation of patients with a history of adverse cutaneous drug reactions, it is important to obtain a detailed medication therapy including over-the-counter drugs, herbal and neuropathic remedies. There are a significant number of offending drugs causing adverse cutaneous drug reactions. If we can find out the clinical pattern of drug reaction along with their risk and aggravating factors, a good number of lives can be saved. If the offending drugs can be identified, proper preventive measures can be taken by individual or policy makers. Many of the cutaneous drug reactions can be prevented if diagnosed early. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13618 Bangladesh J Medicine 2010; 21: 90-95